Optimization Of Multiple Objectives in The Machining Process of SS304 Sheet Metal Components. - Janardan Rathod, Nikhil; B. M, Praveen; Gitay, Mayur; N. Patil, Sidhhant; Patel, Mohan T. (Journal of Neonatal Surgery, 2025)
A comprehensive investigation has been conducted on the settings for the turning operation of SS 304. This study utilizes the Grey-Based Taguchi method to explore the multi-objective optimization of the turning process, aiming to determine the optimal combination of settings that results in the shortest production time and the longest tool life. The parameters examined include feed rate, cutting speed, and depth of cut. To address the multi-response optimization challenge, nine experimental runs were performed based on Taguchi’s L9 orthogonal array, followed by a Grey relational analysis. The Grey relational grade value was employed to ascertain the most effective parameter levels. Additionally, the analysis of variance (ANOVA) will play a crucial role in identifying the key parameters among speed, feed, and cut depth.